Poverty Reduction and Growth Trust : 2017 Borrowing Agreements with the Bank of Spain, the Government of Japan and the People's Bank of China. (Policy Papers; Policy Paper ;, 2017)
the Poverty Reduction and Growth Trust (PRGT or Trust), has entered into a new borrowing agreement with the Bank of Spain (Spain), amendments to the 2010 NPA with the Government of Japan (Japan), and a new note purchase agreement (NPA) with the People's Bank of China (China). The new borrowing agreement with Spain, the amendments to the NPA with Japan, and the new NPA with China provide new resources of SDR 450 million, SDR 1.8 billion and SDR 800 million, respectively, to the General Loan Account of the PRGT for a total amount of SDR 3.05 billion in new PRGT lending resources. The new borrowing agreement, the augmentation under the amended NPA and the new NPA are among the first ten loan contributions concluded in the context of the current Board endorsed effort to raise SDR 11 billion in new PRGT loan resources. These became effective on February 22, 2017, for Spain; April 20, 2017, for Japan; and April 21, 2017, for China. Pursuant to Section III, paragraph 2 of the Instrument to establish the PRGT, the Managing Director is authorized to enter into borrowing agreements and agree to their terms and conditions with lenders to the Loan Accounts of the Trust. This paper presents to the Executive Board for information the new borrowing agreement with Spain, the amendments to augment the existing agreement with Japan, and the new NPA with China. The new borrowing agreement with Spain and NPA with China incorporate the following recent changes to the Fund's framework for concessional lending to low income countries, which have also been adopted, as applicable, in prior amendments to the agreement with Japan: (i) the extensions of the commitments and drawdown period for PRGT loans to end-2020 and end-2024, respectively; (ii) the incorporation of the Chinese Renminbi (RMB) interest rate instrument of six month maturity for borrowing agreements in currencies; and (iii) the provision that, if the derived six-month SDR interest rate formula results in a negative rate, the applicable interest rate shall be zero percent. With respect to the amendment of the NPA with Japan, in addition to increasing the principal amount of notes that can be issued under the NPA, Japan's agreement was also modified to: (i) provide more flexibility in the media of payment for purchases under the NPA; (ii) set up a maximum amount for monthly purchases under the NPA; and (iii) to establish a preferred media for payments of interest and principal amount of the notes issued under the NPA. Except for these changes, all other elements of the NPA with Japan remain unchanged.